Being in safe hands: Patients' perceptions of how cancer services may support psychological well‐being. (25th March 2018) - Appleton, Lynda; Poole, Helen; Wall, Christine
Abstract: Aims: To explore how cancer services may positively promote and support patients' well‐being throughout treatment. Specifically to identify components of care that are important to patients and meet their needs. Background: Patients commonly experience stress and uncertainty during their cancer journey which can have a negative impact on their psychological health and quality of life. Comparatively, little is known about how patients may experience positive well‐being during their treatment experience. Design: Qualitative study using semi‐structured interviews. Methods: Interviews were conducted between 2014 – 2015 with a purposive sample of 30 individuals who were at the beginning, middle or end of treatment for lung, colorectal and head and neck cancer. The majority were outpatients and receiving radiotherapy, chemotherapy or a combination of these. The recordings were analysed using thematic analysis. Results: Patients may obtain a range of positive health benefits derived from contact with staff, patients and public. Positive emotional gains were based on "being in safe hands" and part of the collective effort to eradicate cancer. This appeared to assist patients achieve favourable treatment responses, however, a range of factors encouraged and hindered them to express concerns. Conclusion: Interactions with staff, patients and the hospital environment supported well‐being in those receiving cancer treatment. Findings demonstrate additional areas for research including the development of interventions to facilitate peer support and the implementation of communication strategies that promote well‐being.